Organy polskiej administracji państwowej w Królestwie Polskim 1916–1918. Struktura i gabinety - Goclon, Jacek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The rebirth of the Polish state during World War I was mainly connected with acquisition of fresh recruit soldiers for the armies of Germany and the Habsburg Empire. The goverments in Berlin and Vienna turned their attention to the Polish nation living in the former territories of tsarist Russia, lost to Germany and Austria in 1915 during the war. The only way to convince the Polish nation to cooperate was a clear promise of the rebirth of Polish goverment in these territories and of full independence of the new Polish state after the war. The first step, as a proxy solution, was the Temoporary Civil Council, next the State Council, created in 1916. Soon the members of the council (including Józef Piłsudski) have decided to stop their activity, because the German and Austian goverments failed to keep their promises. The next step was a joint announcement of two emperoros, German and Austrian, which on 5 November 1917 proclamed the Kingdom of Poland, with Regency Council as a goverment. During one year of its activity, the Regency Council created three cabinets with the following three Prime Ministers: Jan Kucharzewski, Jan Steczkowski and Józef Świeżyński. The scope of activity and real power of this cabinets were very limited, but they constituted a beginning of the process of creation and rebirth of the Polish independent state and of education of the future administrative team for the first central independent Polish State.
Keywords: Józef Świeżyński; Prime Minister of Polish Goverments; Regent Council; Temporary Comission; Jan Kucharzewski; Ministery Council; Jan Steczkowski; Temoporary Civil Council; Crown Council